Colorado water, July-September 1985 - Miller, Shirley, editor; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1985)
Newsletter of the Colorado Water Resources Research Institute.
Keywords: Water resources development -- Colorado; Water-supply -- Colorado; Water use -- Colorado; Water-supply -- Management -- Colorado